Problem-Based Learning Strategies As The Main Concept of Quality Learning - Nur Jannah (FALASIFA : Jurnal Studi Keislaman, 2022)
One of the current learning problems is the lack of educators in mastering strategies or learning models that lead to the quality of the learning output itself. The application of methods in learning is one of the keys to achieving quality learning because, in its implementation, the strategy will determine whether the teaching is effective or not. Problem Based Learning (PBL) strategy is one of the strategies considered important in achieving the quality of education because it is based on social and scientific problems by the tendencies of the learner, resulting in a contextual and scientific understanding. In this learning model, students are invited to solve some issues and find solutions for the contextual problems. Thus, students can be actively involved in the learning process so that learning does not feel monotonous and only listens to the teacher lecturing. This strategy indirectly also fosters students' ability to analyze problem-solving and think critically about solving problems or events they will face. This paper examines the concept of quality learning problem-based learning in the idea of quality, both absolute and relative, as Edward Sallis argues. So that learning does not feel monotonous and only listen to the teacher lecturing.